Spanien heute: Politik - Wirtschaft - Kultur - Bernecker, Walther L.; Oehrlein, Josef (Vervuert, 1991)
Walther L. Bernecker/Josef Oehrlein (Hrsg.): "Spanien heute". Politik, Wirtschaft, Kultur. Verlag Vervuert, Frankfurt am Main, 1991. 549 S., kt., 56,- DM